Negative electrode material, preparation method thereof and lithium ion battery
By forming a cladding layer on the surface of natural graphite and adjusting relevant parameters, the problem of deterioration in the performance of natural graphite in high-temperature storage is solved, and better high-temperature storage and cycling performance are achieved.
Patent Information
- Application Number
- CN202411967131.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The performance of natural graphite deteriorates during high-temperature storage, mainly due to its large number of reactive sites, resulting in frequent side reactions.
By forming a cladding layer on the surface of natural graphite and adjusting the compression index, Young's modulus and electrolyte contact angle of the negative electrode material, particle aggregation and side reactions are reduced.
It effectively improves the high-temperature storage performance of natural graphite, reduces the occurrence of side reactions, and improves the mechanical strength and cycling performance of the negative electrode material.
Smart Images

Figure CN119764404A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Natural graphite has excellent kinetic properties, especially low-temperature kinetics, which is due to its abundant pores that facilitate electrolyte infiltration and provide end-face lithium insertion. At the same time, the surface of natural graphite also has abundant functional groups, which can promote the rapid desolvation of organic lithium. However, these factors also lead to more reactive sites in natural graphite, which is prone to more side reactions, greatly deteriorating its high-temperature storage performance.
[0003] Therefore, it is necessary to provide a negative electrode material that improves the high temperature storage performance of natural graphite while retaining the kinetic advantages of natural graphite. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a negative electrode material and a preparation method thereof and a lithium ion battery to improve the problem of deterioration of high temperature storage performance of natural graphite.
[0005] To achieve the above-mentioned object and other related objects, the present invention provides a negative electrode material in a first aspect, wherein the negative electrode material comprises natural graphite and a coating layer coated on the surface of the natural graphite, and the compression index K of the negative electrode material is: 30≤K≤80; wherein the compression index K=100(V 0 -V F ) / V 0 , where V 0 is the apparent volume per unit mass in loose state, V F is the tapped volume per unit mass.
[0006] In one embodiment of the present invention, the Young's modulus E of the negative electrode material is 17 GPa≤E≤25 GPa.
[0007] In one embodiment of the present invention, the contact angle θ between the electrolyte and the surface of the negative electrode material is 82°≤θ≤90°.
[0008] In one embodiment of the present invention, the mass of the coating layer accounts for 0.5% to 1% of the mass of the natural graphite; the material of the coating layer includes aluminum oxide or titanium oxide, and the particle size Dv50 of the aluminum oxide or the titanium oxide is less than 0.1 μm.
[0009] In one embodiment of the present invention, the particle size Dv50 of the negative electrode material is 5 μm to 20 μm.
[0010] A second aspect of the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:
[0011] The natural flake graphite raw material is crushed and shaped to obtain a first precursor;
[0012] Thermally shaping the first precursor and removing surface functional groups to obtain a second precursor;
[0013] The second precursor is subjected to a cold quenching treatment, and a coating layer is formed on the surface of the cold quenched precursor to obtain a negative electrode material.
[0014] In one embodiment of the present invention, the step of thermally shaping the first precursor and removing surface functional groups includes:
[0015] Heating the first precursor to a first temperature;
[0016] Then, the first precursor is subjected to hydroxylation treatment by using deionized water, wherein the amount of the deionized water added is 1% to 3% of the mass of the first precursor;
[0017] Then, the first precursor is subjected to peroxidation treatment by using an oxygen-containing gas, wherein the oxygen-containing gas is a mixed gas of nitrogen and oxygen, and the mass content of oxygen in the mixed gas is 10% to 40%;
[0018] Then, the temperature is raised to a second temperature, and the gas is pumped out until the gas pressure is lower than 0.2 atmospheres and then kept warm for 4 hours, wherein the first temperature is 450°C to 600°C, and the second temperature is 800°C to 1000°C.
[0019] In one embodiment of the present invention, the step of forming a coating layer on the surface of the precursor after cold quenching includes: ball milling the cold quenched material with γ-type alumina for 1h to 3h, then calcining it at 700°C to 900°C in an inert atmosphere for 4h to 8h, and then cooling it to room temperature to obtain a negative electrode material; the particle size Dv50 of the γ-type alumina is less than 0.1μm, and the amount of the γ-type alumina is less than or equal to 1% compared to the mass of the second precursor.
[0020] In one embodiment of the present invention, the cold quenching treatment is to use an inert gas to cool the second precursor, the temperature difference between the cold quenching treatment temperature and the previous treatment temperature is 400°C to 600°C, and the flow rate of the inert gas is less than or equal to 60L / min; and / or the particle size Dv50 of the first precursor is 15μm to 25μm, and the particle size distribution width (Dv90-Dv10) / Dv50 is less than 1.1.
[0021] A third aspect of the present invention provides a lithium-ion battery, the lithium-ion battery comprising a negative electrode plate, the negative electrode plate comprising any of the above-mentioned negative electrode materials or a negative electrode material prepared by any of the above-mentioned preparation methods.
[0022] The negative electrode material of the present invention has suitable powder fluidity by adjusting its compression index, which means that the functional groups on the surface of the negative electrode material particles are reduced, the force between adjacent particles is small, it is easy to disperse during processing, and the possibility of particle agglomeration is reduced. At the same time, the fewer functional groups on the surface reduce the side reactions of the negative electrode material during high-temperature storage, thereby improving the high-temperature storage performance of the negative electrode material. In addition, the Young's modulus of the negative electrode material is adjusted to give it a certain mechanical strength, reduce the generation of microcracks during cold pressing, reduce its reaction activity ratio during high-temperature storage, and further improve the high-temperature storage performance of the negative electrode material. In addition, the contact angle between the negative electrode material and the electrolyte is adjusted to reduce its wettability to the electrolyte, thereby reducing the reaction activity ratio during high-temperature storage, and further improving the high-temperature storage performance of the negative electrode material.
[0023] The present invention uses natural flake graphite as a raw material when preparing the negative electrode material, and sequentially undergoes processes such as thermal shaping, removal of surface functional groups, and cold quenching, so that the negative electrode material has a suitable compression index while maintaining the kinetic performance advantages of natural graphite, thereby reducing the possibility of agglomeration of the negative electrode material, reducing side reactions during high-temperature storage, and improving the high-temperature storage performance of the negative electrode material. The preparation method of the present invention can effectively improve the problem of deterioration of the high-temperature storage performance of natural graphite, and is simple and easy to operate, greatly reducing the cost and energy consumption of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0025] Figure 1 FIG. 4 is a flow chart of a method for preparing a negative electrode material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and the features in the embodiments can be combined with each other without conflict. The test methods for which specific conditions are not specified in the following embodiments are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0028] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0029] In this article, the compression index refers to GB / T 6609.25-2023 to test the tap density and bulk (loose) density, and then the apparent volume and tap volume are calculated according to the formula ρ = m / v, and then K = 100 (V 0 -V F ) / V 0 Calculate the compression index; Young's modulus refers to the GB / T 34186-2017 test; contact angle refers to the GB / T 36086-2018 test.
[0030] Natural graphite has a rich pore structure, which is convenient for electrolyte infiltration and provides lithium insertion space. At the same time, the rich functional groups on the surface of natural graphite can promote the rapid desolvation of organic lithium. These characteristics make natural graphite have excellent kinetic properties, but at the same time, it will also make more reactive sites, resulting in more side reactions, thereby deteriorating the high-temperature storage performance of natural graphite. The existing methods for improving the storage performance of natural graphite include: filling natural graphite with impregnated asphalt and then graphitizing it to reduce the pores of natural graphite; using ultra-high temperature graphitization to passivate the graphite surface, etc. These methods will affect the kinetic properties of natural graphite.
[0031] Based on this, the present invention provides a negative electrode material, a method for preparing the negative electrode material, and a lithium ion battery comprising the negative electrode material. By controlling the compression index K of the negative electrode material to make it have suitable powder fluidity, it is possible to reduce side reactions while maintaining the kinetic advantages of natural graphite, thereby effectively improving the high temperature storage performance of natural graphite.
[0032] The first aspect of the present invention provides a negative electrode material, which includes natural graphite and a coating layer coated on the surface of the natural graphite, and the compression index K of the negative electrode material is 30≤K≤80. Wherein, the compression index K=100(V 0 -V F ) / V 0 , where V0 V is the apparent volume per unit mass of the negative electrode material in a loose state, F is the tap volume per unit mass. The compression index K is used to reflect the flowability of the negative electrode material. The smaller the compression index K, the better the powder flowability of the negative electrode material. The macroscopic manifestation is the smaller the force between the negative electrode material particles, and the microscopic manifestation is that there are fewer functional groups on the surface of the negative electrode material particles, which is easy to disperse during the processing process, reducing the possibility of particle agglomeration. At the same time, the fewer functional groups on the surface of the negative electrode material particles, the fewer side reactions that occur during high-temperature storage, thereby improving the high-temperature storage performance of the negative electrode material. On the contrary, the larger the compression index K, the worse the powder flowability of the negative electrode material, which means that there are more functional groups on the surface of the negative electrode material particles, more side reactions that occur during high-temperature storage, and poor high-temperature storage performance. However, if the compression index is too small, the surface functional groups of the negative electrode material will be almost lost, thereby affecting the kinetic properties of natural graphite itself. Therefore, when the compression index K of the negative electrode material of the present application is controlled within the range of 30≤K≤80, the negative electrode material can reduce the functional groups on its surface while maintaining the kinetic properties of natural graphite, thereby improving its high-temperature storage performance. In some embodiments, the compression index K of the negative electrode material can be 30, 50, 60 or 80, etc.
[0033] In one embodiment, the Young's modulus E of the negative electrode material is 17GPa≤E≤25Gpa. Young's modulus indicates the degree of change in the initial length per unit cross section of the powder after being subjected to a certain tensile stress, which reflects the deformation of the material under stress. The calculation formula of Young's modulus is E=σ / ε, where σ represents the stress per unit area of the material, and ε represents the strain per unit length. It can be seen from the calculation formula of Young's modulus that when the stress σ per unit area of the material remains unchanged, the larger the Young's modulus E, the smaller the strain ε per unit length, indicating that the material is less likely to deform, that is, the greater the mechanical strength; conversely, the smaller the Young's modulus E, the larger the strain ε per unit length, indicating that the material is more easily deformed, that is, the smaller the mechanical strength. The negative electrode material will undergo lithium ion embedding and extraction during the charge and discharge process of the lithium-ion battery. If the mechanical strength of the negative electrode material is low (the material is soft), a large volume deformation will occur during the lithium ion embedding and extraction process, and it will not recover, which is not conducive to the cycle of the lithium-ion battery; while the mechanical strength of the negative electrode material is high (having a certain hardness), the microscopic crystal structure can be better maintained during the lithium ion extraction process, and a small irreversible deformation will occur, so that the lithium-ion battery has better cycle performance; but the hardness of the negative electrode material is too large, on the one hand, it is not easy to compact, and it may also produce microcracks, increasing the reaction activity ratio in high temperature storage. Therefore, the Young's modulus E of the negative electrode material is controlled within a suitable range to maintain good mechanical strength, reduce the generation of microcracks in the cold pressing process, reduce the reaction activity ratio in high temperature storage, and also have better cycle performance. In some embodiments, the Young's modulus E of the negative electrode material can be 17GPa, 20Gpa, 22Gpa or 25Gpa, etc.
[0034] In one embodiment, the contact angle θ between the electrolyte and the surface of the negative electrode material is 82°≤θ≤90°. The contact angle θ is the reciprocal of the radius of curvature of a minimal surface formed by the liquid surface on the solid surface when the liquid contacts the solid surface. It is an important parameter for measuring the wettability of the liquid on the solid surface. When the contact angle θ is less than 90°, the solid surface is hydrophilic, and the liquid is easier to wet the solid. The smaller the angle, the better the wettability, and the larger the angle, the worse the wettability. The contact angle θ of the electrolyte on the surface of the negative electrode material of the present application is 82°≤θ≤90°, which can reduce the wettability of the electrolyte to the negative electrode material, thereby reducing the reaction activity ratio during high-temperature storage, and further improving the high-temperature storage performance of the negative electrode material. Exemplarily, the contact angle θ can be 82°, 85°, 88° or 90°, and so on. It should be noted that the electrolyte here is an electrolyte commonly used in lithium-ion batteries, and the solvent of the electrolyte includes but is not limited to dimethyl carbonate. The electrolyte used in this application is manufactured by Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., and the model is E3.
[0035] In one embodiment, the material of the coating layer may be aluminum oxide or titanium oxide. Further, the coating layer material is aluminum oxide. Aluminum oxide coated on the surface of natural graphite can reduce the contact between natural graphite and electrolyte, reduce side reactions, and improve the high temperature stability of the negative electrode material; on the other hand, the true density of aluminum oxide is relatively large, and the Young's modulus and compactness of the negative electrode material can also be increased.
[0036] In one embodiment, the particle size Dv50 of the negative electrode material is 5 μm to 20 μm. Dv50 represents the particle size corresponding to when the cumulative volume distribution reaches 50% in the particle size distribution. For example, the particle size Dv50 of the negative electrode material can be listed as 5 μm, 10 μm, 15 μm or 20 μm, etc.
[0037] The second aspect of the present invention provides a method for preparing a negative electrode material. The negative electrode material prepared by the preparation method has a lower compression index, so that the negative electrode material has suitable powder fluidity, reduces the possibility of particle agglomeration and side reactions occurring during high-temperature storage.
[0038] See also Figure 1 The method for preparing the negative electrode material comprises at least the following steps:
[0039] S1, crushing and shaping the natural flake graphite raw material to obtain a first precursor;
[0040] S2, thermally shaping the first precursor and removing surface functional groups to obtain a second precursor;
[0041] S3, subjecting the second precursor to cold quenching treatment, and forming a coating layer on the surface of the precursor after cold quenching to obtain a negative electrode material.
[0042] Specifically, step S1 uses natural flake graphite as raw material, and pre-treats it before crushing and shaping it to remove impurity minerals in the raw material. The pre-treatment includes water washing and flotation. First, the natural flake graphite is washed with water to remove dirt, dust and other impurities on the surface of the graphite, in preparation for the subsequent flotation process. Flotation adds flotation agents to make the selective attachment of graphite particles and other impurity minerals on the water surface different, thereby separating graphite from other minerals and improving the purity of natural flake graphite.
[0043] Since the particle size of natural flake graphite is relatively large, which can reach the micron or even millimeter level, the natural flake graphite needs to be crushed and shaped after pretreatment to obtain a first precursor with a suitable particle size distribution. Specifically, it includes: high-frequency shaping of the natural flake graphite after water washing and flotation, so that the millimeter-level natural flake graphite size Dv50 is reduced to 15-25μm, and the larger and smaller sizes are removed by graded manner, so that the particle size distribution width (Dv90-Dv10) / Dv50 is less than 1.1. The above-mentioned high-frequency shaping can adopt conventional shaping methods in the art, such as using a honeycomb mill to shape the natural flake graphite at a high frequency of 90Hz for 6 hours. The honeycomb mill can effectively disperse and depolymerize the aggregated graphite flakes, reduce the damage to large flake graphite, and improve the quality of graphite products. It should be noted that Dv90 represents the particle size corresponding to 90% of the cumulative volume distribution in the particle size distribution; Dv10 represents the particle size corresponding to 10% of the cumulative volume distribution in the particle size distribution. The particle size distribution width (Dv90-Dv10) / Dv50 is an indicator to measure the uniformity of particle size. The larger the particle size distribution width, the wider the particle size distribution, that is, the greater the difference between large particles and small particles; the closer the particle size distribution width is to 0, the more uniform the particle size and the higher the size consistency. Step S1 reduces the particle size Dv50 of natural flake graphite to 15-25μm, and the particle size distribution width (Dv90-Dv10) / Dv50<1.1 can make the final negative electrode material meet its use particle size. Exemplarily, the Dv50 of the first precursor can be 15μm, 20μm or 25μm, etc.; the particle size distribution width (Dv90-Dv10) / Dv50 can be 1, 0.5 or 0, etc.
[0044] Step S2 removes the functional groups on the surface of the first precursor, specifically comprising: first collecting the first precursor obtained in step S1 and transferring it to a jet mill and heating it to a first temperature to remove the crystal water in the first precursor. The first temperature is 450°C to 600°C, for example, 450°C, 500°C or 600°C. Then, deionized water is pumped in to hydroxylate the first precursor to remove some impurity functional groups such as ester groups and acyl groups, wherein the amount of deionized water added accounts for 1% to 3% of the mass of the first precursor, and illustratively, the amount of deionized water added can be 1%, 2% or 3%. Then, ventilation is maintained for ultra-high frequency thermal shaping, the shaping frequency is 100Hz to 140Hz, for example, 100Hz, 120Hz or 140Hz, and the thermal shaping time is 0.5h to 2h, for example, 0.5h, 1h, 1.5h or 2h. After the thermal shaping is completed, an oxygen-containing gas is introduced from the upper end of the gas flow mill to peroxidize the first precursor to form oxygen-containing functional groups that are easy to fall off, wherein the oxygen-containing gas is a mixed gas of nitrogen and oxygen, and the mass content of oxygen in the mixed gas is 10% to 40%, for example, 10%, 20%, 30% or 40%. The flow rate of the oxygen-containing gas is 2L / min, and ventilation is maintained for 4 hours while shaping. After the ventilation is stopped, the temperature is raised to the second temperature and the air is pumped out to remove the oxygen-containing functional groups formed in the above steps. The second temperature is 800 to 1000°C, illustratively, it can be 800°C, 900°C or 1000°C, etc. After the pressure in the chamber is less than 0.2 atmospheres, it is kept warm for 4 hours to stabilize the crystal form to obtain a second precursor.
[0045] Then, step S3 is performed to quench the second precursor obtained in step S2 to obtain a negative electrode material with a certain mechanical strength. The quenching treatment is to use an inert gas to perform a gradient cooling on the second precursor, and the inert gas can be nitrogen, helium or argon. Gradient cooling means cooling to a certain temperature and keeping it for a period of time; then cooling to another temperature and keeping it for a period of time, and so on, until the set temperature is reached. The temperature difference of each quenching treatment is not easy to be too large, and too large a temperature difference is easy to produce microcracks inside the graphite. The temperature difference of the quenching treatment in the present invention is 400-600°C, specifically 400°C, 500°C, or 600°C. The number of quenching treatments is at least once. If the number is too many, the improvement is not large, but it will cause energy consumption. The flow rate of the inert gas is less than or equal to 60L / min, and further 30L / min to 60L / min. Exemplarily, it can be 30L / min, 40L / min, 50L / min or 60L / min. If the flow rate of the inert gas is greater than 60L / min, it will cool down instantly, causing defects such as microcracks inside the material.
[0046] After the cold quenching treatment is completed, a coating layer is formed on the surface of the precursor. In one embodiment, the material of the coating layer is aluminum oxide, and the coating process of aluminum oxide is as follows:
[0047] The material after cold quenching is ball-milled with γ-alumina for 1h to 3h, and then calcined at 700℃ to 900℃ in an inert atmosphere for 4h to 8h, and then cooled to room temperature in an inert atmosphere to obtain a natural graphite negative electrode material with alumina coated on the surface. The calcination temperature can be listed as 700℃, 800℃ or 900℃, and the calcination time can be listed as 4h, 6h or 8h. γ-alumina is used because γ-alumina is unstable and can be converted into stable α-alumina by chemical adsorption on the graphite surface and reacting with the dangling bonds on the graphite surface. The particle size Dv50 of the above-mentioned γ-alumina is less than 0.1μm. The smaller the particle size, the easier it is to adsorb on the graphite surface to form a uniform alumina coating layer. The amount of γ-alumina is less than or equal to 1% of the mass of the second precursor, further 0.5~1%, and further 0.8%. The negative electrode material is a layer of aluminum oxide coated on the surface of natural graphite. The aluminum oxide coating can avoid direct contact between natural graphite and electrolyte, reduce side reactions, and improve the stability of the negative electrode material. In addition, since the above-mentioned defunctionalization step will greatly reduce the wettability of electrolyte to electrolyte, which is not conducive to the lithium ion transmission inside the battery, the aluminum oxide coating can improve the wettability of electrolyte to negative electrode material.
[0048] In other embodiments, the coating layer material may be replaced with titanium dioxide. The coating process of titanium dioxide may refer to conventional processes in the art and will not be described in detail here.
[0049] After the above steps, the particle size Dv50 of the negative electrode material obtained is 5 μm to 20 μm. For example, the particle size Dv50 of the negative electrode material can be 5 μm, 10 μm, 15 μm or 20 μm.
[0050] The negative electrode material prepared by the above preparation method has a smaller compression index, a higher Young's modulus and a suitable contact angle, and has excellent high-temperature storage performance while maintaining the dynamics of natural graphite.
[0051] The third aspect of the present invention provides a lithium ion battery, which includes a non-aqueous electrolyte lithium battery, a solid lithium battery, etc. Taking a non-aqueous electrolyte lithium battery as an example, the lithium ion battery includes a negative electrode sheet, a positive electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet includes the above-mentioned negative electrode material of the present invention or the negative electrode material prepared by the above-mentioned preparation method.
[0052] Specifically, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode current collector can use conventional materials in the art, such as copper foil, carbon-coated copper foil, etc. The negative electrode active material layer can be provided on one surface of the negative electrode current collector or on both surfaces. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. Among them, the negative electrode active material is selected from materials capable of intercalating and deintercalating lithium ions. In the present invention, the negative electrode active material is the above-mentioned negative electrode material. In other embodiments, the negative electrode active material can also be selected as a combination of the above-mentioned negative electrode material and other materials, such as silicon-based negative electrode materials. The silicon-based negative electrode materials include silicon oxides SiO x (0 < x < 2), silicon-carbon materials, silicon单质, etc. However, this application is not limited to the materials listed above, and other traditional materials that can be used as negative electrode active materials can also be used. These negative electrode active materials can be used alone or in combination of two or more. The negative electrode conductive agent can improve the electronic conductivity and play a role in collecting microcurrents between the negative electrode active materials and between the negative electrode active material and the negative electrode current collector to reduce the contact resistance of the battery and accelerate the electron movement rate. In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotube, graphene. Optionally, the negative electrode conductive agent is conductive carbon black; or, a composition of carbon fiber and conductive carbon black; or, a composition of carbon nanotube and graphene, etc. The binder is used to bond the negative electrode active material and the negative electrode conductive agent and provide a certain adhesive force for the negative electrode active material layer to bond it to the negative electrode current collector. As an example, the negative electrode binder is selected from at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), styrene-acrylate, acrylic acid-based multi-component copolymer. For example, the negative electrode binder is polyvinylidene fluoride, or a composition of styrene-butadiene rubber and carboxymethyl cellulose, etc. The proportions of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder can refer to the conventional settings in the art.
[0053] An example of the preparation process of the negative electrode plate is as follows: First, the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder are mixed and stirred evenly in a solvent such as deionized water according to a certain ratio to form a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode current collector. After processes such as drying, rolling, and cutting, a negative electrode plate is obtained.
[0054] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector may be made of conventional materials in the art, such as aluminum foil, carbon-coated aluminum foil, etc. The positive electrode active material layer may be disposed on the surface of one side of the positive electrode current collector, or on the surface of both sides. The positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, wherein the positive electrode active material may be selected from any positive electrode material suitable for lithium-ion batteries, that is, compounds that can reversibly embed and deintercalate lithium ions may be used. As an example, the positive electrode active material may be a ternary material, such as a nickel-cobalt-manganese ternary material (NCM), a nickel-cobalt-aluminum ternary material (NCA), etc., and the iron-lithium positive electrode material may be, for example, lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), etc., and may also be a traditional material such as lithium cobalt oxide, lithium manganese oxide, etc. These materials may be used alone or in combination. The positive electrode binder is, for example, any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene-butadiene rubber (SBR), etc. The positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotubes, and graphene. Optionally, the conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotubes and graphene, etc. The ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can refer to the conventional settings in the art.
[0055] The preparation process of the positive electrode sheet is exemplified as follows: first, the positive electrode active material, the positive electrode conductor and the positive electrode binder are mixed and stirred in a solvent such as N-methylpyrrolidone (NMP) in a certain ratio to form a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector. After drying, rolling, cutting and other processes, the positive electrode sheet is obtained.
[0056] The diaphragm is set between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode to prevent short circuit inside the battery, and at the same time allow lithium ions to pass through and move between the positive and negative electrodes to realize the battery's charge and discharge process. The diaphragm can be made of porous materials such as polyethylene film (PE), polypropylene film (PP), glass fiber film or composite film. The thickness of the diaphragm is 9 to 18μm, the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%.
[0057] Lithium-ion batteries also include an electrolyte, which conducts lithium ions during the battery charge and discharge process. The electrolyte includes an organic solvent and a lithium salt, which can be selected from lithium hexafluorophosphate (LiPF 6), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). Further, the lithium salt selects lithium hexafluorophosphate or a combination of lithium hexafluorophosphate and other lithium salts with better comprehensive performance, such as a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The organic solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC). The electrolyte may also include functional additives, such as fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), vinylene carbonate (VC), vinyl sulfate (DTD), etc., which can be added according to the needs in actual production.
[0058] Battery assembly: Place the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to isolate them, and obtain a bare cell by winding or stacking. Put the bare cell into the battery shell, and obtain a lithium-ion battery after assembly, injection, formation, and capacity division.
[0059] In other embodiments, the lithium-ion battery may also be a solid-state lithium-ion battery. The electrolyte of the solid-state lithium-ion battery is solid. Common solid-state electrolytes are oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, etc., which are not elaborated here. Those skilled in the art can make a selection according to actual production needs.
[0060] It should be noted that the structures not described in detail in the above lithium-ion battery can be configured with reference to the prior art and will not be described in detail here.
[0061] The lithium-ion battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0062] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0063] Example 1
[0064] The present embodiment provides a negative electrode material, which includes natural graphite and aluminum oxide, wherein the aluminum oxide is uniformly coated on the surface of the natural graphite, and the coating amount of the aluminum oxide accounts for 1% of the mass of the natural graphite; the compression index K of the negative electrode material is 54, the Young's modulus E is 21Gpa, and the contact angle θ is 85°; the particle size Dv50 of the negative electrode material is 12.7μm.
[0065] This embodiment also provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:
[0066] Step 1: The natural flake graphite after water washing and flotation is subjected to 90Hz high-frequency shaping for 6 hours using a honeycomb mill to reduce the millimeter-level natural flake graphite size Dv50 to 15-25μm, and gradedly remove larger and smaller sizes to make its particle size distribution width (Dv90-Dv10) / Dv50 1.0, thereby obtaining a first precursor;
[0067] Step 2: Collect the powder of the first precursor and transfer it to the airflow mill and heat it to T1:600℃. Pump in deionized water at a mass ratio of 50:1 (the amount of deionized water added is 2% of the mass of the first precursor) and then perform 120Hz ultra-high frequency shaping for 2h. Then introduce a mixed gas of 600℃ nitrogen and oxygen (mass ratio 4:1, the mass percentage of oxygen in the mixed gas is 20%) from the upper end of the airflow mill. The flow rate of the mixed gas is L1:2L / min. Keep ventilation for 4h and shape at the same time; after stopping ventilation, heat it to T2:800℃ and evacuate the air outward. After the pressure in the chamber is less than 0.2 atmospheres, keep it warm for 4h to obtain the second precursor. Then introduce inert gas from the upper end of the airflow mill and cool it down to T3:200℃. The flow rate of inert gas L2: is 60L / min. Keep ventilation for 2h, then stop heating to obtain a spherical precursor.
[0068] Step 3: ball-mill the above-mentioned spherical precursor with γ-alumina for 2 hours; the particle size of γ-alumina is less than 0.1μm, the amount is 1wt%, and the sphericity of the finished product is greater than 0.93 after ball-milling for 2 hours; calcined at 800℃ for 6h under an inert atmosphere, cooled to room temperature under an inert atmosphere, and obtained a finished product of 12.7μm.
[0069] Referring to Table 1, the present invention further provides Examples 2 to 9 and Comparative Examples 1 to 5.
[0070] Example 2
[0071] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 67, the Young's modulus E is 23 Gpa, the contact angle θ is 83°; and the particle size Dv50 of the negative electrode material is 13.1 μm.
[0072] In the preparation method, the amount of deionized water added during the hydroxylation treatment is 1%, and the rest remains unchanged.
[0073] Example 3
[0074] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 42, the Young's modulus E is 21 Gpa, the contact angle θ is 88°; and the particle size Dv50 of the negative electrode material is 12.5 μm.
[0075] In the preparation method, the amount of deionized water added during the hydroxylation treatment is 3%, and the rest remains unchanged.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 75, the Young's modulus E is 25 Gpa, the contact angle θ is 82°; and the particle size Dv50 of the negative electrode material is 13.5 μm.
[0078] In the preparation method, the mass percentage of oxygen in the mixed gas during the peroxidation treatment is 40%.
[0079] Example 5
[0080] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 35, the Young's modulus E is 20 Gpa, the contact angle θ is 90°; and the particle size Dv50 of the negative electrode material is 12.4 μm.
[0081] In the preparation method, the mass percentage of oxygen in the mixed gas during the peroxidation treatment is 10%.
[0082] Example 6
[0083] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 30, the Young's modulus E is 17 Gpa, the contact angle θ is 87°; and the particle size Dv50 of the negative electrode material is 12.3 μm.
[0084] In the preparation method, the temperature T2 during the outward exhaust is adjusted to 1000°C. During the cold quenching treatment, the temperature is first lowered to 600°C with inert gas and the ventilation is maintained for 2 hours. Then, the temperature is lowered to 200°C with inert gas and the ventilation is maintained for 2 hours.
[0085] Example 7
[0086] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 30, the Young's modulus E is 17 Gpa, the contact angle θ is 88°; and the particle size Dv50 of the negative electrode material is 12.1 μm.
[0087] In the preparation method, the temperature during the outward exhaust is raised to 900°C, and the quenching temperature is 300°C.
[0088] Example 8
[0089] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 80, the Young's modulus E is 19 Gpa, and the contact angle θ is 90°; the particle size Dv50 of the negative electrode material is 13 μm;
[0090] In the preparation method, the amount of γ-alumina used in step 3 is 0.5%.
[0091] Example 9
[0092] The difference between this embodiment and embodiment 1 is that: the compression index K of the negative electrode material is 68, the Young's modulus E is 21 Gpa, and the contact angle θ is 87°; the particle size Dv50 of the negative electrode material is 13.3 μm;
[0093] In the preparation method, the amount of γ-alumina used in step 3 is 0.8%.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that the compression index K of the negative electrode material is 26, the Young's modulus E is 17 Gpa, the contact angle θ is 90°; and the particle size Dv50 of the negative electrode material is 11.6 μm.
[0096] The exhaust temperature in step 2 of the preparation method is increased to 1250°C.
[0097] Comparative Example 2
[0098] The difference between this comparative example and Example 1 is that the compression index K of the negative electrode material is 123, the Young's modulus E is 30 Gpa, the contact angle θ is 102°; and the particle size Dv50 of the negative electrode material is 15.4 μm.
[0099] In the preparation method, no temperature increase step is performed before the vacuum temperature is pumped out.
[0100] Comparative Example 3
[0101] This comparative example uses commercially available conventional 12 μm natural graphite. The negative electrode material of this comparative example has a compression index K of 138, a Young's modulus E of 2 Gpa, a contact angle θ of 74°, and a particle size Dv50 of 11.2 μm.
[0102] Comparative Example 4
[0103] The difference between this comparative example and Example 1 is that the compression index K of the negative electrode material is 95, the Young's modulus E is 15 Gpa, the contact angle θ is 81°; and the particle size Dv50 of the negative electrode material is 12.7 μm.
[0104] The amount of γ-alumina used in step three of the preparation method is 0.2%.
[0105] Comparative Example 5
[0106] The difference between this comparative example and Example 1 is that: the compression index K of the negative electrode material is 106, the Young's modulus E is 15 Gpa, and the contact angle θ is 80°; the particle size Dv50 of the negative electrode material is 10.5 μm; and the surface of natural graphite is not coated with aluminum oxide.
[0107] There are no steps 3 and 4 in the preparation method.
[0108] Table 1: Parameter characteristics and preparation method parameters of negative electrode materials of Examples 1-9 and Comparative Examples 1-5
[0109]
[0110]
[0111] In order to verify the performance of the negative electrode material of the present invention, the inventors applied the negative electrode materials of Examples 1-9 and Comparative Examples 1-5 in lithium ion batteries, and performed performance tests on each lithium ion battery. The composition and test method of the lithium ion battery are as follows. The test results are shown in Table 2.
[0112] The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet, the separator and the negative electrode sheet are wound to obtain a battery cell, which is then packaged in a packaging shell and injected with an electrolyte to obtain a soft-pack battery.
[0113] Among them, the preparation of the negative electrode sheet: the negative electrode material obtained in the embodiment or the comparative example, the conductive agent (SP), the binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and the thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.2:0.5:1.8:0.5 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the copper foil; and then after drying, rolling, cutting and other processes, a negative electrode sheet is prepared.
[0114] Preparation of positive electrode sheet: The positive electrode active material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O 2 ), PVDF and SP are mixed in a mass ratio of 97:1.8:1.2 (a total of 100 parts by mass), and 82 parts by mass of NMP are added to obtain a positive electrode slurry; the obtained positive electrode slurry is coated on at least one surface of an aluminum foil, dried, and rolled to obtain.
[0115] Diaphragm: It is a polyethylene film with a thickness of 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0116] The electrolyte used was a commercial electrolyte (manufacturer: Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model: E3).
[0117] Battery performance test method
[0118] (1) Full battery first effect
[0119] Full battery charging capacity: Charge the lithium-ion battery to 4.35V with a current of 1C, record the charging capacity at this stage as c1, and then charge at a constant voltage until the cut-off current is 0.05C. The charging capacity at this stage is c2, and the full battery charging capacity is the sum of c1 and c2.
[0120] Full battery discharge capacity: Fully charge the cell, rest for 30 minutes, then discharge to 2.8V with 1C current, and record the discharge capacity c3 at this stage, which is the full battery discharge capacity.
[0121] First effect = full battery discharge capacity c3 / full battery charge capacity (c1 + c2) × 100%.
[0122] (2) Fast charging time
[0123] Directly charge to 8% SOC state with 0.33C current, and then test the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80% according to the actual measurement of the three-electrode window of the battery cell, which are c1, c2, c3, c4, c5, c6, c7, and c8 respectively. Use stepcharge to charge to 80%, that is, 8%-10% with c1, 10% to 20% with c2, and so on. Record the charging time from 8% to 80% SOC state as the measure of fast charging capability. The calculation formula is:
[0124] T(8%-80%)=(0.02 / c1+0.1 / c2+0.1 / c3+0.1 / c4+0.1 / c5+0.1 / c6+0.1 / c7+0.1 / c8)*60.
[0125] (3)Number of cycles at room temperature
[0126] At 25°C, the material was cycled at 0.21A / g (calculated based on the mass of the positive electrode active material) and 2.8-4.25V. The number of cycles when the initial capacity reached 80% was recorded as the material cycle performance effect.
[0127] (4) Storage days
[0128] At 25°C, the capacity is fixed with a current of 0.33C and recorded as C0. The cells are then stored at a high temperature of 60°C. After that, the cells are taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2, ..., Cn, until Cn is less than or equal to 80% of C0 for the first time. The number of days is used as a measure of the storage capacity and is recorded as storage days.
[0129] Table 2: Performance of assembled batteries of Examples 1-9 and Comparative Examples 1-5
[0130]
[0131] It can be seen from Tables 1-2 that the compression index, Young's modulus and contact angle of the negative electrode material can be adjusted by adjusting parameters such as hydroxylation treatment, peroxidation treatment, cold quenching treatment and the coating amount of aluminum oxide during the preparation process. The compression index of the negative electrode materials obtained in Examples 1 to 9 is significantly reduced compared to the currently commercially available natural graphite (Comparative Example 3), indicating that the negative electrode material of the present invention has suitable powder fluidity, and the functional groups on the surface of the negative electrode material particles are reduced, thereby reducing side reactions during battery cycling and storage, and improving the battery's cycling and storage performance. The cycle performance and high temperature storage performance of the assembled battery at room temperature are significantly improved compared to Comparative Example 3. Although the fast charging performance is slightly reduced, the overall performance of the battery is significantly improved. The compression index of the negative electrode materials of Comparative Examples 1-2 and Comparative Example 4 are not within the scope specified in this application, and the assembled batteries are increased compared to Comparative Example 3, but the first effect, fast charging time, cycle performance and storage performance are all poor compared to Examples 1-9. The negative electrode material of Comparative Example 5 contains natural graphite, and the surface of the natural graphite is not coated with alumina. The functional groups on the surface of the natural graphite are completely exposed, and the powder fluidity is poor. Therefore, the compression index is high, and the exposure of the surface functional groups leads to an increase in side reactions, resulting in relatively poor high-temperature storage performance.
[0132] The negative electrode material provided by the present invention has suitable powder fluidity by adjusting the compression index, the functional groups on the surface of the negative electrode material are reduced, the force between adjacent particles is small, it is easy to disperse during processing, and the possibility of particle agglomeration is reduced. At the same time, the fewer functional groups on the surface reduce the side reactions during high-temperature storage, thereby improving the high-temperature storage performance of the negative electrode material. In addition, the negative electrode material has a higher Young's modulus, so that it has a certain mechanical strength, reduces the generation of total microcracks during the cold pressing process, reduces the reaction activity ratio during high-temperature storage, and further improves the high-temperature storage performance of the negative electrode material. And the contact angle between the negative electrode material and the electrolyte is large, which reduces the wettability of the electrolyte to the negative electrode material, thereby reducing the reaction activity ratio during high-temperature storage, and further improving the high-temperature storage performance of the negative electrode material. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0133] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode material, characterized in that: include: Natural graphite and a coating layer coated on the surface of the natural graphite; the compression index K of the negative electrode material is: 30≤K≤80; wherein the compression index K=100(V0-V F ) / V0, where V0 is the apparent volume per unit mass in the loose state, V F is the tapped volume per unit mass.
2. The negative electrode material according to claim 1, characterized in that The Young's modulus E of the negative electrode material is: 17GPa≤E≤25GPa.
3. The negative electrode material according to claim 1 or 2, characterized in that: The contact angle θ between the electrolyte and the surface of the negative electrode material is: 82°≤θ≤90°.
4. The negative electrode material according to claim 1, characterized in that The mass of the coating layer accounts for 0.5% to 1% of the mass of the natural graphite; the material of the coating layer includes aluminum oxide or titanium oxide, and the particle size Dv50 of the aluminum oxide or titanium oxide is less than 0.1 μm.
5. The negative electrode material according to claim 1, characterized in that The particle size Dv50 of the negative electrode material is 5 μm to 20 μm.
6. A method for preparing the negative electrode material according to claim 1, characterized in that: The following steps are involved: The natural flake graphite raw material is crushed and shaped to obtain a first precursor; Thermally shaping the first precursor and removing surface functional groups to obtain a second precursor; The second precursor is subjected to a cold quenching treatment, and a coating layer is formed on the surface of the cold quenched precursor to obtain a negative electrode material.
7. The method for preparing the negative electrode material according to claim 6, characterized in that: The step of thermally shaping the first precursor and removing surface functional groups comprises: heating the first precursor to a first temperature; Then, the first precursor is subjected to hydroxylation treatment by using deionized water, wherein the amount of the deionized water added is 1% to 3% of the mass of the first precursor; Then, the first precursor is subjected to peroxidation treatment by using an oxygen-containing gas, wherein the oxygen-containing gas is a mixed gas of nitrogen and oxygen, and the mass content of oxygen in the mixed gas is 10% to 40%; Then, the temperature is raised to a second temperature, and the gas is pumped out until the gas pressure is lower than 0.2 atmospheres and then kept warm for 4 hours, wherein the first temperature is 450°C to 600°C, and the second temperature is 800°C to 1000°C.
8. The method for preparing the negative electrode material according to claim 6, characterized in that: The step of forming a coating layer on the surface of the precursor after cold quenching includes: ball milling the cold quenched material with γ-type alumina for 1h to 3h, then calcining it at 700°C to 900°C in an inert atmosphere for 4h to 8h, and then cooling it to room temperature to obtain a negative electrode material; the particle size Dv50 of the γ-type alumina is less than 0.1μm, and the amount of the γ-type alumina is less than or equal to 1% compared to the mass of the second precursor.
9. The method for preparing the negative electrode material according to claim 6, characterized in that: The quenching treatment is to cool the second precursor by using an inert gas, the temperature difference between the quenching treatment temperature and the previous treatment temperature is 400° C. to 600° C., and the flow rate of the inert gas is less than or equal to 60 L / min; And / or, the particle size Dv50 of the first precursor is 15 μm to 25 μm, and the particle size distribution width (Dv90-Dv10) / Dv50<1.
1.
10. A lithium ion battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the preparation method according to any one of claims 6 to 9.